A Game Theoretic Model for Wireless Sensor Networks with Hidden-Action Attacks. (1st August 2013) - Mao, Yuxin; Zhu, Ping; Wei, Guiyi
The unattended nature of wireless sensor networks makes them very vulnerable to an adversary's malicious attack. In this paper, we propose to apply game theory into solving the network security problem of wireless network. We explore game theory algorithms to model situation for wireless network with malicious nodes and investigate the attack and detection problem by modeling it as pairwise simultaneous game and spatial structured game. We consider the relationship between the nodes in a wireless sensor network to formulate the game and give the game theory algorithms in detail. We also evaluate the approach with a simulation experiment and analyze the simulation results in detail. We argue that the approach is able to support secure end-to-end communication in wireless sensor networks.